One-step solution method for the preparation of organic-inorganic hybrid perovskite (CH 3 NH 3 ) 2 PbI 4 Ultrathin nanosheets approach
The preparation of organic-inorganic hybrid perovskite (CH3NH3) 2PbI4 nanosheets was solved by a one-step solution method, which solved the problem of difficulty in preparing ultra-thin nanosheets in the prior art, and achieved the preparation of nanosheets with the thinnest thickness of 2.1 nanometers, simplified the process and promoted its application in the two-dimensional field.
Patent Information
- Application Number
- CN202310889153.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-07-19
AI Technical Summary
It is difficult to effectively prepare ultra-thin organic-inorganic hybrid perovskite (CH3NH3) 2PbI4 nanosheets in the prior art, and the preparation process is complicated.
By using a one-step solution method, by weighing a specific proportion of the precursor raw material and solvent, adding an appropriate amount of additives, stirring at a specific temperature, the solution is dropped onto a silicon substrate using a dropper, and after a standstill and evaporating process, ultra-thin perovskite nanosheets were finally observed under an optical microscope.
The ultra-thin preparation of organic-inorganic hybrid perovskite (CH3NH3) 2PbI4 nanosheets is realized, with a thickness of up to 2.1 nanometers, simplifying the preparation process and promoting its application in the two-dimensional field.
Smart Images

Figure CN117142957B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an organic-inorganic hybrid perovskite ultra-thin nanosheet by a solution method, and belongs to the field of material science. Background Art
[0002] Organic-inorganic hybrid perovskite materials have been widely studied due to their high light absorption / emission efficiency, large defect tolerance, long carrier diffusion length, and high flexibility. Among them, ultrathin organic-inorganic hybrid perovskite materials are expected to become excellent new flexible materials and be applied in related fields because they combine the excellent properties of hybrid components and two-dimensional morphology. Compared with organic-inorganic hybrid perovskites with three-dimensional morphology, two-dimensional ultrathin perovskites have strong quantum confinement effects, high luminescence yields, low amplified spontaneous emission thresholds, easily tunable band gaps, high exciton binding energy, and strong thickness dependence, making them easier to apply to flexible integrated devices [National Science Review, 9, nwab129, 2022].
[0003] Generally, two-dimensional ultra-thin organic-inorganic hybrid perovskite materials can be obtained by solution method, mechanical stripping method, chemical vapor deposition and other methods. Among them, the solution method has the advantages of large output, simple process and low price. However, the thickness of organic-inorganic hybrid perovskite materials currently prepared based on the solution method is relatively thick, or the preparation steps are complicated. At present, the growth of (CH3NH3)2PbI4 materials is mainly polycrystalline thin films with a thickness of the micron order. Organic-inorganic hybrid perovskite materials with similar chemical formulas or structures are mostly grown by mechanical stripping, chemical vapor deposition or two-step solution method, with a minimum thickness of more than 10 nanometers. Other polycrystalline films grown by methods such as scraping are generally in the micron order of thickness. Therefore, if a simple method for preparing two-dimensional ultra-thin organic-inorganic hybrid perovskites can be invented, it will greatly promote the development of its related applications. Summary of the invention
[0004] The technical problem solved by the present invention is: in order to solve the difficulty in preparing ultra-thin nanosheets of organic-inorganic hybrid perovskite (CH3NH3)2PbI4, the present invention uses a simple one-step solution method to prepare ultra-thin organic-inorganic hybrid perovskite (CH3NH3)2PbI4 nanosheets, with the thinnest thickness reaching 2.1 nanometers, which is of great significance to the application of organic-inorganic hybrid perovskite in the field of two-dimensional integration.
[0005] The present invention provides a method for preparing an organic-inorganic hybrid perovskite (CH3NH3)2PbI4 nanosheet using a one-step method. Up to now, there are almost no reports that ultrathin (CH3NH3)2PbI4 nanosheets can be prepared using a solution method. Compared with the (CH3NH3)2PbI4 nanosheet obtained by a mechanical stripping method, the nanosheet obtained by the present invention can reach 2.1 nanometers, which can greatly promote its application in the two-dimensional field. In particular, in response to the demand for miniaturization of devices in the post-Moore era, based on the excellent optoelectronic properties inherent to organic-inorganic hybrid perovskites, the perovskite nanosheet can be applied to micro-nano photoelectric detection devices, lasers, light-emitting diodes and other fields in the future, and due to its small size, it is conducive to integration in various micro-devices, flexible wearable devices and other aspects.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: a method for preparing organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheets by a one-step solution method, comprising the following steps:
[0007] S1: Weigh 2-5 g of precursor raw materials CH3NH3I and PbI2 powder respectively, the weight ratio of CH3NH3I and PbI2 powder is 1:2, put them in 5-15 ml of solvent HI, and add 1-3 ml of additive methylamine ethanol or ethanol solution;
[0008] S2: Stir the above solution at 20-50°C for 1-3 hours;
[0009] S3: Use a disposable dropper to absorb the above solution and drop it on the silicon substrate, cover it with a cover glass and a slide glass respectively, place a 500-800 g weight on it, and let it stand for 1-4 hours;
[0010] S4: Remove the weight, slide and cover glass respectively, place the substrate at 50-60°C for evaporation for 10-60 minutes, and ultra-thin perovskite nanosheets can be observed on the substrate through an optical microscope.
[0011] Preferably, the method comprises the following steps:
[0012] S1: Weigh 2 g of precursor raw material CH3NH3I and 4 g of PbI2 powder, place in 10 ml of solvent HI, and add 2 ml of additive ethanol solution;
[0013] S2: Stir the above solution at 40°C for 2 hours;
[0014] S3: Use a disposable dropper to absorb the above solution and drop it on the silicon substrate, cover it with a cover glass and a slide glass respectively, place an 800 g weight on it, and let it stand for 3 hours;
[0015] S4: Remove the weight, slide and cover glass respectively, place the substrate at 55°C for evaporation for 40 minutes, and ultrathin perovskite nanosheets can be observed on the substrate through an optical microscope.
[0016] In order to solve the above technical problems, another technical solution proposed by the present invention is: organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheets prepared by the method described.
[0017] Preferably, the thickness of the obtained organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheet is 2.1 nanometers.
[0018] In order to solve the above technical problems, another technical solution proposed by the present invention is: the application of the organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheets prepared by the method described, the obtained organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheets have a thickness of 2.1 nanometers, and the perovskite nanosheets can be applied to micro-nano photoelectric detection devices, lasers, and light-emitting diodes, and due to their small size, they are conducive to integration into various micro devices and flexible wearable devices.
[0019] Beneficial effects:
[0020] The present invention is based on a one-step solution method and utilizes the principle of gravity confinement to achieve the growth and preparation of ultra-thin nanosheets of organic-inorganic hybrid perovskite (CH3NH3)2PbI4, with a minimum thickness of 2.1 nanometers. This is of great significance for the integrated application based on this material, especially for the demand for continuous miniaturization of devices in the current post-Moore era. Ultra-thin nanosheets are of great significance to the development of device miniaturization.
[0021] The present invention provides a method for preparing ultra-thin nanosheets of organic-inorganic hybrid perovskite (CH3NH3)2PbI4 by a one-step solution method. Up to now, there are almost no reports that can achieve the growth of ultra-thin nanosheets of the material. At present, the growth of the material is mainly polycrystalline thin film with a thickness of micrometer order. Materials with similar chemical formulas or structures are mostly grown by mechanical stripping, chemical vapor deposition or two-step solution method, with a minimum thickness of more than 10 nanometers. Other polycrystalline thin films grown by methods such as scraping and coating are generally micrometer-order thick.
[0022] Compared with the (CH3NH3)2PbI4 nanosheets obtained by mechanical stripping, the nanosheets obtained by the present invention can reach 2.1 nanometers, which can greatly promote its application in the two-dimensional field. In particular, in response to the demand for miniaturization of devices in the post-Moore era, based on the excellent photoelectric properties inherent in organic-inorganic hybrid perovskites, the perovskite nanosheets can be applied to micro-nano photoelectric detection devices, lasers, light-emitting diodes and other fields in the future, and due to their small size, they are conducive to integration in various micro-devices, flexible wearable devices and other aspects.
[0023] It can be seen from Examples 1-5 that the thickness of the organic-inorganic hybrid perovskite (CH3NH3)2PbI4 nanosheet grown and prepared in Example 1 is the thinnest, and its thickness is 2.1 nanometers as measured by atomic force microscopy (see Appendix Figure 2 ), the photoluminescence center peak is 751 nanometers (see attached Figure 3 ), and the X-ray diffraction spectrum shows its excellent crystal quality (see Appendix Figure 4 ). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an optical photograph of the nanosheet in Example 1.
[0025] Figure 2 This is an atomic force microscope image of the nanosheet in Example 1.
[0026] Figure 3 This is the photoluminescence spectrum of the nanosheet in Example 1.
[0027] Figure 4 This is the X-ray diffraction spectrum of the nanosheets in Example 1. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the embodiments.
[0029] Embodiment 1:
[0030] A method for preparing organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultrathin nanosheets using a one-step solution method, the specific implementation steps are as follows:
[0031] S1: Weigh 2 g of precursor raw material CH3NH3I and 4 g of PbI2 powder, place them in 10 ml of solvent HI, and add 2 ml of additive ethanol solution; the above raw materials were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0032] S2: Stir the above solution at 40°C for 2 hours;
[0033] S3: Use a disposable dropper to absorb the above solution and drop it on the silicon substrate, cover it with a cover glass and a slide glass respectively, place an 800 g weight on it, and let it stand for 3 hours;
[0034] S4: Remove the weight, glass slide and cover glass respectively, place the substrate at 55°C for evaporation for 40 minutes, and observe the ultrathin perovskite nanosheets on the substrate through an optical microscope (see Appendix). Figure 1 ), and its thickness was found to be 2.1 nanometers by atomic force microscopy (see Appendix Figure 2 ), the photoluminescence center peak is 751 nanometers (see attached Figure 3), and the X-ray diffraction spectrum shows its excellent crystal quality (see Appendix Figure 4 ).
[0035] Embodiment 2:
[0036] A method for preparing organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultrathin nanosheets using a one-step solution method, the specific implementation steps are as follows:
[0037] The additive was changed to methylamine ethanol solution, and the other steps were the same as those in Example 1. The thickness of the nanosheets obtained by this method was 10-20 nanometers.
[0038] The additive was changed to aqueous solution, and the other steps were the same as in Example 1. This method could not produce perovskite nanosheets.
[0039] When other steps are the same, the average thickness of the nanosheets obtained by using ethanol as an additive is thinner than that obtained by using the same volume of methylamine ethanol.
[0040] In Example 1, if the HI solvent is replaced with a solvent such as dimethylformamide or dimethyl sulfoxide commonly used to grow organic-inorganic hybrid perovskites, the perovskite nanosheets cannot be obtained.
[0041] Example 3
[0042] A method for preparing organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultrathin nanosheets using a one-step solution method, the specific implementation steps are as follows:
[0043] The amounts of ethanol additive tried were 1, 1.5, 2, 2.5, and 3 ml, and the other steps were the same as in Example 1.
[0044] Among them, 2 ml of ethanol gave the thinnest nanosheets, with the thinnest being 2.1 nanometers. Too little or too much ethanol would increase the thickness. When the amount of ethanol was 1, 1.5, 2.5, and 3 ml, the thickness of the nanosheets on the substrate ranged from 20-50 nanometers, 5-30 nanometers, 10-40 nanometers, and 30-60 nanometers, respectively. When the amount of ethanol was greater than 3 ml, nanosheets with regular morphology could not be obtained or no nanosheets could be obtained.
[0045] Example 4
[0046] A method for preparing organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultrathin nanosheets using a one-step solution method, the specific implementation steps are as follows:
[0047] In step S3, the weight of the legal weight is changed to 100, 200, 300, 400, 500, 600, 700, 800, 900, or 1000 grams, and the other steps are the same as those in Example 1.
[0048] When 800 grams of weight is placed, the thickness of the nanosheet is the smallest, the minimum is 2.1 nanometers. As the weight of the weight decreases, the thickness increases sharply. When the weight of the weight is 100, 200, 300, 400, 500, 600, and 700 grams, the corresponding nanosheet thickness range is greater than 1 micron, 200-1000 nanometers, 100-500 nanometers, 50-150 nanometers, 30-100 nanometers, 20-50 nanometers, and 10-30 nanometers. When the weight is not placed, a polycrystalline film is obtained, and no nanosheet grows. When the weight of the weight is 900 grams and 1000 grams, due to the excessive pressure given by the weight, the cover glass has cracks or warps, and the nanosheet is thicker (greater than 500 nanometers) or no nanosheet grows. When the weight of the weight is greater than 1000 grams, the cover glass is easily broken and no nanosheet grows.
[0049] Example 5
[0050] A method for preparing organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultrathin nanosheets using a one-step solution method, the specific implementation steps are as follows:
[0051] The mass of the precursor raw material PbI2 was changed to 1, 2, 3, and 5 grams, and the other steps were the same as in Example 1.
[0052] The thickness of the nanosheets obtained by this method is very thick (the thickness ranges from 15 to 50 nanometers, 5 to 20 nanometers, 8 to 15 nanometers, and 10 to 50 nanometers) or no nanosheets can be obtained.
[0053] In Example 1, the weight ratio of CH3NH3I and PbI2 powder should be 1:2. If it is changed to other ratios (4:1, 3:1, 2:1, 1:1, 1:1.5, 1:2.5, 1:3, 1:4 and other ratios have been tried), the perovskite nanosheets cannot be obtained.
[0054] Example 6
[0055] In S1 of Example 1, if the amount of solvent HI is too little, the thickness of the grown nanosheets will increase dramatically (the thickness is generally greater than 30 nanometers); if the amount is too much, the morphology of the grown nanosheets will deteriorate; if the amount is too much in excess, no nanosheets can be grown.
[0056] When HI is 5-8 ml, the thickness is relatively large, generally greater than 30 nm. When HI is 11-15 ml, the morphology of the nanosheet becomes worse. When HI exceeds 15 ml or is less than 5 ml, the nanosheet cannot be grown.
[0057] Example 7
[0058] In S2 of Example 1, if the stirring temperature is too high, the morphology of the grown nanosheets becomes poor and is not a regular shape. When the temperature is higher than 50°C, due to the strong temperature sensitivity of the organic-inorganic hybrid perovskite, the perovskite nanosheet cannot be grown. If the temperature is too low, the morphology of the grown nanosheets is poor. When the temperature is lower than 20°C, it is impossible to ensure that the precursor raw material powder is completely dissolved, and the substrate after growth is large particles without nanosheets.
[0059] Example 8
[0060] In S2 of Example 1, the stirring time is higher than 3 hours, which is basically the same as that of stirring for 1-3 hours to finally obtain nanosheets. Considering the time and energy consumption cost, a stirring time of less than 3 hours is more appropriate. However, if the stirring time is too short, less than 1 hour, the powder cannot be completely dissolved, a large number of solid particles are present on the obtained substrate, the nanosheet morphology is poor, and due to the presence of large-sized particles, the thickness of the nanosheet is very thick.
Claims
1. A method for preparing organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultrathin nanosheets using a one-step solution method, characterized in that: The following steps are involved: S1: Weigh 2-5 g of precursor raw materials CH3NH3I and PbI2 powder respectively, the weight ratio of CH3NH3I and PbI2 powder is 1:2, put them in 5-15 ml of solvent HI, and add 1-3 ml of additive methylamine ethanol or ethanol solution; S2: Stir the above solution at 20-50 °C for 1-3 hours; S3: Use a disposable dropper to absorb the above solution and drop it on the silicon substrate, cover it with a cover glass and a slide glass respectively, place a 500-800 g weight on it, and let it stand for 1-4 hours; S4: Remove the weight, glass slide and cover glass respectively, place the substrate at 50-60 °C for evaporation for 10-60 minutes, and observe the organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheet with a thickness of 2.1 nanometers on the substrate through an optical microscope.
2. The method for preparing organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheets by a one-step solution method according to claim 1, characterized in that: The following steps are involved: S1: Weigh 2 g of precursor raw material CH3NH3I and 4 g of PbI2 powder, place in 10 ml of solvent HI, and add 2 ml of additive ethanol solution; S2: Stir the above solution at 40 °C for 2 hours; S3: Use a disposable dropper to absorb the above solution and drop it on the silicon substrate, cover it with a cover glass and a slide glass respectively, place an 800 g weight on it, and let it stand for 3 hours; S4: Remove the weight, slide and cover glass respectively, place the substrate at 55 °C for evaporation for 40 minutes, and the perovskite nanosheets can be observed on the substrate through an optical microscope.
3. Organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultrathin nanosheets prepared according to the method of claim 1 or 2.
4. Application of the organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheet prepared by the method according to claim 3, characterized in that: The obtained organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheet has a thickness of 2.1 nanometers. The perovskite nanosheet is used in micro-nano photoelectric detection devices, lasers, and light-emitting diodes.
5. Application of the organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultra-thin nanosheet prepared by the method according to claim 3, characterized in that: The obtained organic-inorganic hybrid perovskite (CH3NH3)2PbI4 ultrathin nanosheet has a thickness of 2.1 nanometers. The perovskite nanosheet can be used for integration into various micro-devices and flexible wearable devices.
Citation Information
Patent Citations
Organic-inorganic composite perovskite material single crystal film and preparation method and application thereof
CN108023017A
Preparation method of highly stable lead-based organic-inorganic hybrid perovskite nano sheet
CN110194718A